Informal Methods for Improving Students' Senior High School Arabic Language Skills - Zaky Anwar; Lailatul Mauludiyah (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study aims to improve the Arabic speaking skill of students in class XI MIA 4 MA Al-Ittihad Belung, Poncokusumo. This study is an experiment of an informal method used in Arabic to improve students' Arabic speaking skills. This research is quantitative. This type of research is a pre-experiment with a one-group pre-test and post-test design method. The research instruments used were observation and interviews. Data collection techniques used interview tests in the form of pre-tests and posttests. The paired sample t test was used to analyze the research data. The result of the t test statistic is 0.001 < 0.05, then  is accepted. So, it can be concluded that there is a significant difference between the pre-test and post-test conducted. In this case, it can be said that learning Arabic with informal methods can help students improve their ability to speak Arabic at MA Al-Ittihad Belung, Poncokusumo, Malang.